PENGARUH ZAT KIMIA PADA BERBAGAI SUHU TERHADAP DENYUT JANTUNG KATAK (Rana sp.) DALAM UPAYA PENGEMBANGAN BUKU PETUNJUK PRAKTIKUM FISIOLOGI HEWAN - Sry Purnamasari; Muhammad Wahyu Setiyadi (Bioscientist : Jurnal Ilmiah Biologi, 2019)
The purpose of this study is to determine the effect of chemicals on various temperatures in the heart of frogs (Rana sp.) And to compile valid animal physiology practical instructions. This research is a type of experimental research (true experimental) and this research approach is a qualitative approach. Samples were given 3 different treatments, namely controls with room temperature of 250C-300C, temperature of 00C-100C, and 300C-400C. The results of the study using ANOVA (Analysis of Variance) showed the effect of NaCl solution on the frog heart rate (Rana sp.) Namely Fcount of 5.18 while Ftable of 3.59 so that the results of this study were declared significant. While the effect of saline solution on the frog heart rate (Rana sp.) Is Fcount of 1.78 while Ftable is 3.59 so the results of this study are declared non-significant. So it can be concluded that, NaCl solution at various temperatures significantly influences the frog heart rate (Rana sp.), While saline solution at various temperatures does not significantly influence the frog heart rate (Rana sp.). The process of developing this animal physiology practical guide uses a 3-D development model, which consists of the define, design, and develope stages. The results of the study showed that the practicum instructions for animal physiology were valid, said to be valid because the practicum instructions prepared and developed had met the "valid" criteria.